Harvest time, planting time: Writing in and by living in the countryside (Research, Society and Development, 2021)
In Brazilian society, an ideal of devaluation of rural people was established, as if they were ragged individuals with little schooling. Thus, it is up to the rural schools to meet the demands of the peasant community and also demystify this ideology loaded with preconceptions attributed to workers and people living in rural areas. The present study reports an interdisciplinary experience developed with students of the 3rd year of Elementary Education, from the Roberval Costa Reis State School, located in the Porto Velho settlement, municipality of Santa Terezinha / MT. The pedagogical intervention aimed to provide them with activities and mediation that would make it possible to consolidate scientific and sign literacy, in addition to literacy for life, starting from the local context. The action was carried out during the second semester of 2018 and went through six stages, in which theoretical and practical activities were worked, focused on the production of food on the properties, stimulating learning to read and write mathematical concepts and sciences from the beginning. knowledge of the world and its reality. During the proposed activities, it can be seen that students were more motivated to participate in the actions developed in the classroom, and especially when they broke through that quadrilateral, reaching spaces that were rarely used for the purpose of promoting school learning, such as the laboratory. computer science, the schoolyard and the backyards of the existing houses in the school community. Finally, the actions made it possible for us to expand the universe of possibilities for integrating knowledge with regard to literacy and literacy of these subjects of law.